Sprache im italienischen Erdkundeunterricht Eine multiperspektivische Studie - Schöber, Stephanie (Verlag Barbara Budrich, 2017)
The author examines linguistic challenges faced by learners at the end of lower secondary level in subject education. Her empirical data come from schools in Italy. It identifies discrepancies between learners' use of language and the registers used in textbooks and by teachers. The analyses focus on vocabulary and explore other linguistic aspects and the role of language educators.